Exploring the potential for public involvement in health research in Singapore - Luna Puerta, Lidia (Nanyang Technological University, 2020)
Despite growing evidence of the positive impact of public involvement, formally referred to as patient and public involvement (PPI), in research, this remains rare in Singapore. The potential of PPI in the Singapore-Asia context has to be explored. I conducted a three-phased exploratory study aiming to: 1) set the background through a mapping review of published articles and grey literature, including media reports, 2) provide a national perspective through a qualitative study guided by thematic framework analysis and 3) provide a study perspective through a case study of involvement in a local biobank study using the Theoretical Domains Framework. An iterative research process was adopted throughout all phases, enabling findings from each phase to be integrated. Phase 1 highlighted a shift towards patient-centeredness in Singapore, both in clinical curriculum and practices, and a desire to continue the road of patient activation and engagement. The shift for the clinical aspect could facilitate a shift in research-oriented tasks. Phase 2 revealed that most interviewees (n = 40) expressed a lack of experience with PPI, which was perceived as a beneficial strategy, both by researchers and by lay members. Whilst highlighting both utilitarian and ethical reasons for implementing PPI, challenges specific to the Singapore-Asia context made involvement at an individual level less likely to be successful. Interviewees - researchers from diverse disciplines and levels of experience, and with roles in funding panels and ethics boards, and lay members of diverse background and ages - identified formal and informal strategies to overcome barriers, favouring an asset-based, more community-oriented approach.